2024
DOI: 10.2341/23-124-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Varied Silane Commercial Brands and Adhesive Application on Bond Strength and Stability to Lithium Disilicate Glass Ceramic

ET Calixto,
VF Kelmer,
GH Komegae
et al.

Abstract: SUMMARY Objectives: This study aimed to evaluate the impact of various commercial silane brands with varied chemical compositions with or without the application of an adhesive layer on the microshear bond strength and durability of a resin luting agent to lithium disilicate glass ceramic. Methods and Materials: Lithium disilicate glass ceramic discs (EMX, IPS e.max Press, Ivoclar Vivadent) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The composite resin to be used should be applied, choosing the appropriate material for each case [2,3]. Some work, analyzing the relevance of various chemical and mechanical treatments in old composite resins and repair bond strength, concluded that the improvement in the bond strength between the new and the old composite resin restoration requires increased harshness to institute micromechanical union between the surface of the old composite resin and the resin together [4,5].…”
Section: Major Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite resin to be used should be applied, choosing the appropriate material for each case [2,3]. Some work, analyzing the relevance of various chemical and mechanical treatments in old composite resins and repair bond strength, concluded that the improvement in the bond strength between the new and the old composite resin restoration requires increased harshness to institute micromechanical union between the surface of the old composite resin and the resin together [4,5].…”
Section: Major Outcomesmentioning
confidence: 99%
“…The use of drills, followed by acid etching and application of adhesive, appears to be used by more than 80% of dentists as a pre-treatment of the old composite to be repaired. In vitro data can help elucidate whether silane treatment of composite resin surfaces before repair is indispensable [3][4][5].…”
Section: Introductionmentioning
confidence: 99%